Immunohistochemical localization of the calcitonin gene-related peptide binding site in the primate trigeminovascular system using functional antagonist antibodies. (22nd July 2016) - Miller, Silke; Liu, Hantao; Warfvinge, Karin; Shi, Licheng; Dovlatyan, Mary; Xu, Cen; Edvinsson, Lars
Highlights: Antibodies against the CLR/RAMP1 extracellular domains block CGRP binding and function in vitro . Antibodies display specificity in Western blot and immunohistochemistry applications. Immunohistochemistry localizes CGRP receptors at key sites in the trigeminovascular system. Abstract: Calcitonin gene-related peptide (CGRP) is a potent vasodilator and a neuromodulator implicated in the pathophysiology of migraine. It binds to the extracellular domains of calcitonin receptor-like receptor (CLR) and receptor activity-modifying protein (RAMP) 1 that together form the CGRP receptor. Antagonist antibodies against CGRP and its binding site at the receptor are clinically effective in preventing migraine attacks. The blood–brain barrier penetration of these antagonist antibodies is limited, suggesting that a potential peripheral site of action is sufficient to prevent migraine attacks. To further understand the sites of CGRP-mediated signaling in migraine, we used immunohistochemical staining with recently developed antagonist antibodies specifically recognizing a fusion protein of the extracellular domains of RAMP1 and CLR that comprise the CGRP binding pocket at the CGRP receptor in monkey and man. We confirmed binding of the antagonist antibodies to human vascular smooth muscle cells (VSMCs) of dural meningeal arteries and neurons in the trigeminal ganglion, both of which are likely sites of action for therapeutic antibodies in migraine patients. We further used one of these antibodies for detailed mapping on cynomolgus monkey tissue and found antagonist antibody binding sites at multiple levels in the trigeminovascular system: in the dura mater VSMCs, in neurons and satellite glial cells in the trigeminal ganglion, and in neurons in the spinal trigeminal nucleus caudalis. These data reinforce and clarify our understanding of CGRP receptor localization in a pattern consistent with a role for CGRP receptors in trigeminal sensitization and migraine pathology.